Are we eating plastics? / Yusrina Andu and Shazani Sarijan - Andu, Yusrina; Sarijan, Shazani (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Plastics in Food: The use of plastics is indeed helpful for everyone. It is convenient for shoppers and other industries that require plastic packaging. Unfortunately, the utilisation has now influenced the safety of our daily food [1]. Recently the discovery of microplastics and nanoplastics in food has garnered the attention of various sectors. Micro-/Nano-plastics are defined as the tiny size of plastic particles less than 5 mm [2]. The study begins with plastic particle pollution in the environment, such as water and sediments [3]. However, the study extends to edible aquatic animals, canned foods, table salts and vegetables. It can also be found in bottled water and other food commodities [4]. Yes, the researchers found plastic in our daily food!